Personnel protection : executive worksite security, proven practices - Miller, Jerome (Elsevier, 2013)
In Personnel Protection: Executive Worksite Security, presenters Jerome Miller and Radford Jones discuss the potential security risks to executives while at the office and en route to the office. This seven-minute presentation of narrated slides includes recommendations for controlling access to areas of particular concern, such as installing fencing, monitoring the premises using a closed-circuit television (CCTV) system, conducting visitor screening, and installing bullet-resistant glass doors and duress alarms. This presentation is one of 11 modules in the Personnel Protection presentation series, which is designed for companies considering an executive security program or for companies with an executive security program already in place.